Dochody z gospodarstw rolniczych w województwie warmińsko-mazurskim przed akcesją Polski do Unii Europejskiej - Kucka, Elżbieta; Stempel, Ryszard (Incomes from Agriculture Farms in Warmia and Mazury Voivodship Before the Accession of Poland to the European Union, 2005)
The research in 150 individual farms in Warmia-Mazury voivodship was done in 2003. Those farms carried out exclusively agricultural activity of multi-directional production. The research concerned the level of incomes gained in farms of different sizes. Agriculture net income from a farm was from 2904 zlotys to 6109 zlotys. The highest agriculture income per one hectare of arable lands (1100 zlotys) was in farms up to 5 hectares while on fully employed (35 935 zlotys) in farms above 50 hectares. The unprofitable incomes' relation of farmers in comparison with incomes of other social groups in Poland is found. This relation was 41,1% in the researched farms in 2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 513-518